Iraq and American empire can Arab-Americans influence Middle East policy? - Khalidi, Rashid (Emirates lecture series, 2007)
To understand the limits of the political influence of Arab-Americans it is essential to understand how poorly assimilated into American society many are. Many of them still do not speak English well; indeed some do not speak any English at all. Many are not citizens, are not registered to vote and have never contributed money to political campaigns. This is understandable, since many of them, especially those who are older, did not grow up in the United States, were not educated in American schools, and do not understand how the American political or legal systems work. They come from authoritarian systems, where the state is regarded with suspicion and fear, and where politics is often dangerous. Many inhabit predominantly Arab communities isolated from the larger society around them. It is impossible to predict how soon there may be an increase in the minimal political influence of Arab-Americans at the national level in the United States, but it will happen sooner or later. When it does happen it will change the way that US domestic politics relates to foreign policy issues."--Publisher Summary